2020
DOI: 10.1093/cid/ciaa177
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Weight Gain Following Switch to Integrase Inhibitor–Based Antiretroviral Therapy

Abstract: Background Treatment initiation with integrase strand transfer inhibitors (INSTIs) has been associated with excess weight gain. Whether similar gains are seen after switch to INSTIs among virologically suppressed persons is less clear. We assessed pre/post-INSTI weight changes from AIDS Clinical Trials Group participants (A5001 and A5322). Methods Participants who were in follow-up from 1997–2017 and switched to INSTI-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 15 publications
16
138
6
2
Order By: Relevance
“…Women and persons of black race who received RAL‐based ART experienced greater increases in waist circumference compared to the PI‐based ART recipients. In another study evaluating weight gain following switch to INSTI‐based regimens among virally suppressed ACTG participants in protocols A5001 and A5322, female sex, black race and older age were all associated with greater annualized weight gain after switch to INSTI [26]. Similarly, in the current study we found that female sex, lower baseline weight and lower baseline CD4 were factors associated with significantly higher odds of a >10% weight gain at two and five years after ART initiation.…”
Section: Discussionsupporting
confidence: 78%
“…Women and persons of black race who received RAL‐based ART experienced greater increases in waist circumference compared to the PI‐based ART recipients. In another study evaluating weight gain following switch to INSTI‐based regimens among virally suppressed ACTG participants in protocols A5001 and A5322, female sex, black race and older age were all associated with greater annualized weight gain after switch to INSTI [26]. Similarly, in the current study we found that female sex, lower baseline weight and lower baseline CD4 were factors associated with significantly higher odds of a >10% weight gain at two and five years after ART initiation.…”
Section: Discussionsupporting
confidence: 78%
“…Differences in gender (mainly men) and ethnicity (mainly white) could partly explain this result. By contrast, an analysis of 691 patients with virologic suppression in the ACTG A5551 or A5332 studies from 2007 to 2017 found that women, black people and persons aged ≥60 years experienced a greater rate of weight gain in the 2 years after a switch to an INSTI-based regimen than before the switch 74 . Additionally, in the ANRS163 ETRAL study, 165 persons with viral suppression who switched from a PI to raltegravir and etravirine had a 12% increase in DXA-assessed total, trunk and limb fat but not in lean mass after 96 weeks 75,76 .…”
Section: Generalized Fat Gain and Obesitymentioning
confidence: 96%
“…However, recently, several reports revealed treatment with that some INSTIs resulted in weight gain, both in ART-initiated and ART-experienced patients switched off PIs to INSTI [12,13,[17][18][19][20][21][22]. This may represent an undesirable effect placing patients at higher risk for cardiovascular and metabolic complications on the long term.…”
Section: Introductionmentioning
confidence: 99%